Gereja Metaverse - Winta (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2022)
The purpose of this writing is to see how far the church's readiness is in facing the changing times, especially digital technology. Digital technology is a field that is experiencing very fast development, one of the technologies that is currently being widely discussed is the metaverse. With the presence of the metaverse, it also contributes to the emergence of a new form of worship, namely the metaverse church service. Through this research, the authors hope to be able to prepare the church for a new era of online worship. This study uses qualitative methods with phenomenological analysis.